Strategi Pemasaran: Strategi Bertumbuh di Era Resesi bagi UMKM di Kebumen - Agustini, Dwi Siwi; Setyawati, Harini Abrilia (Universitas Pahlawan Tuanku Tambusai, 2025)
Amidst the global economic challenges caused by the recession, micro, small, and medium enterprises (MSMEs) in Kebumen face significant pressure in maintaining their business sustainability and growth. This training aims to equip the owners and managers of MSMEs, particularly those involved in Rukun (Rumah UMKM Kebumen), with effective and adaptive marketing strategies to thrive during the recession. The training methods include interactive workshops, case studies, and marketing simulations relevant to the local conditions in Kebumen. The results of the training indicate that participants were able to identify new market opportunities, develop creative marketing plans, and enhance their digital skills to expand their marketing reach. This training is expected to make a significant contribution to increasing the competitiveness of MSMEs in Kebumen and inspire innovative and sustainable marketing practices.